The complex impact of China's science and technology talent policies on key core technologies R&D. - Pu Miao; Xiaoyan Zhang; Ning Zhang (PLoS ONE)
Key core technologies have become the focal point of global technological competition. For latecomer countries, formulating effective science and technology talent policies to stimulate researchers' motivation and innovation potential is crucial for mastering these key technologies. This study uses a sample of 1363 publicly listed enterprises in China from 2011 to 2023 to investigate the impact of science and technology talent policies on key core technologies R&D in enterprises. The findings are as follows: (1) Science and technology talent policies significantly promote key core technologies R&D; however, their impact is stronger on non-key core technologies R&D and utility model R&D than on key core technologies R&D. Further study found that non-key core technologies R&D and utility model R&D have a crowding-out effect on key core technologies R&D to a certain extent, and the effect of the former is stronger than that of the latter. (2) As the intensity of policy support increases, its impact on key core technologies R&D also strengthens. Moreover, policies related to talent subsidies, innovation incentives, talent introduction, and high-level talent innovation support all facilitate key core technologies R&D, although the effects vary across these policy types. Moreover, there is no interaction between talent subsidies and innovation incentives, or between talent subsidies and high-level talent innovation support, but there is an offsetting effect between the other policies. (3) The positive impact of science and technology talent policies exhibits a time lag, generally ranging from 4 to 5 years. During this lag period, the effect on the number of patent declines by 8.475% to 28.283%, while the impact on the number of citations of patents decreases by 55.696% to 73.214%. (4) The significant promotional effect of science and technology talent policies is most pronounced in non-state-owned enterprises and those with high R&D investment, but such policies do not have a notable impact on state-owned enterprises or those with low R&D investment. The study demonstrates that latecomer countries can effectively promote key core technologies R&D by designing science and technology talent policies. Based on these findings, recommendations are made to enhance the support intensity of talent policies, optimize the synergistic effects of these policies, extend the duration of policy support, and implement differentiated measures for policy execution.